Vilniaus ir Dysnos apskričių baudžiavinių ūkių raidos XIX a. viduryje statistinė analizė - Pamerneckis, Stasys (Lietuvos istorijos studijos, 1996)
The decay of feudal relations and intensification of commodity production is analysed on the basis of compulsory inventories in the middle of the 19th century. The basis of agricultural economy in Llthuania was the farm estate, based on corvey work in the Vilnius and Dysna districts, complete corvey work prevailed. Peasants, who paid money for the ground, accounted for 9%, and semicorvey peasants was about 15% ofthe total number of serfdom farms. This state of things showed, that the state was not indined to abolish serfdom at this time.